Temporary Work: The Gendered Rise of the Precarious Employment Relationship - Reiter, Ester (Labour / Le Travail, 2002)
The article reviews the book, "Temporary Work: The Gendered Rise of the Precarious Employment Relationship," by Leah F. Vosko.
Keywords: Business And Economics--Labor And Industrial Relations; Employers; Employment; Employment agencies; Gender; History; History--History of North And South America; Labor force; Temporary employment; Workers